Pengaruh Model Pembelajaran PjBL terhadap Kurangnya Pemahaman dan Hasil Belajar Matematika Kelas IV SD GMIM 92 Bailang - Deysti Trifena Tarusu; Regina K. Sarudi (Journal on Education, 2024)
This study aims to determine the effect of the Project-Based Learning (PJBL) learning model on the understanding and learning outcomes of mathematics in fractions material in grade IV of SD GMIM 92 Bailang. The type of research used is quantitative with an experimental design. The subjects of the study consisted of 25 students who took part in mathematics learning using the PJBL model. Data were collected through learning outcome tests and observations to measure the level of students' understanding of fractions material. Data analysis was carried out using statistical tests with the help of SPSS. The results showed that the application of the PJBL learning model had a positive impact on students' understanding and learning outcomes in fractions material, as evidenced by the increase in learning outcome test scores after the model was implemented. Based on statistical tests, there was a significant difference between student learning outcomes before and after learning using PJBL. This study suggests that the PJBL model can be used as an alternative to improve students' understanding and learning outcomes in mathematics, especially in fractions material.